Pengaruh Pengetahuan Wajib Pajak, Sanksi Pajak, Dan penerapan E-Samsat Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Kabupaten Enrekang - Nur Asirah; Nisma Ariskha Masdar (Journal Axegnal: Tax And Economic Insights Journal, 2026)
This study aims to analyze the effect of taxpayer awareness, tax sanctions, and the implementation of e-Samsat on motor vehicle taxpayer compliance in Enrekang Regency. The method used in this study is quantitative with regression analysis. Data were obtained by distributing questionnaires to taxpayers in the area. The results of the study indicate that taxpayer awareness has a positive and significant effect on the level of taxpayer compliance. The higher the understanding and awareness of taxpayers regarding the importance of tax obligations, the more likely they are to comply with these obligations. In addition, the application of strict tax sanctions also contributes to increasing compliance, where sanctions serve as an incentive for taxpayers to fulfill their tax payment obligations. The implementation of the e-Samsat system has been proven to provide convenience in the tax payment process, which also increases convenience and accessibility for taxpayers. This study shows that a combination of tax education, effective enforcement of sanctions, and the application of good information technology can significantly improve tax implementation in the community